Functional ERAP1 Variants Distinctively Associate with Ankylosing Spondylitis Susceptibility under the Influence of HLA-B27 in Taiwanese - Chin-Man Wang; Ming-Kun Liu; Yeong-Jian Jan Wu; Jing-Chi Lin; Jian-Wen Zheng; Jianming Wu; Ji-Yih Chen (Cells, 2022)
Epistasis of ERAP1 single nucleotide variations (SNVs) and HLA-B27 has been linked to ankylosing spondylitis susceptibility (AS). The current study examined how prevalent ERAP1 allelic variants (SNV haplotypes) in Taiwan affect ERAP1 functions and AS susceptibility in the presence or absence of HLA-B27. Sanger sequencing was used to discover all ERAP1 coding SNVs and common allelic variants in Taiwanese full-length cDNAs from 45 human patients. For the genetic association investigation, TaqMan genotyping assays were utilized to establish the genotypes of ERAP1 SNVs in 863 AS patients and 1438 healthy controls. Ex vivo biological analysis of peripheral blood mononuclear cells from homozygous donors of two common-risk ERAP1 allelic variants was performed. Two common-risk ERAP1 allelic variants were also cloned and functionally studied. In Taiwanese, eleven frequent ERAP1 SNVs and six major ERAP1 allelic variants were discovered. We discovered that in Taiwanese, the most prevalent ERAP1-001 variant with 56E, 127R, 276I, 349M, 528K, 575D, 725R, and 730Q interacting with HLA-B27 significantly contributed to the development of AS. In HLA-B27 negative group, however, the second most prevalent ERAP1-002 variant with 56E, 127P, 276M, 349M, 528R, 575D, 725R, and 730E was substantially related with an increased risk of AS. Ex vivo and in vitro research demonstrated that ERAP1 allelic variants have a significant impact on ERAP1 functions, suggesting that ERAP1 plays a role in the development of AS. In an HLA-B27-dependent manner, common ERAP1 allelic variants are related with AS susceptibility.